Selective inhibitor of sodium-calcium exchanger, SEA0400, affects NMDA receptor currents and abolishes their calcium-dependent block by tricyclic antidepressants - Boikov, Sergei I.; Karelina, Tatiana V.; Sibarov, Dmitry A.; Antonov, Sergei M. (Frontiers in Pharmacology, 2024)
The open-channel block of N-methyl-D-aspartate receptors (NMDARs) and their calcium-dependent desensitization (CDD) represent conventional mechanisms of glutamatergic synapse regulation. In neurotrauma, neurodegeneration, and neuropathic pain the clinical benefits of cure with memantine, ketamine, Mg2+, and some tricyclic antidepressants are often attributed to NMDAR open-channel block, while possible involvement of NMDAR CDD in the therapy is not well established. Here the effects of selective high-affinity sodium-calcium exchanger (NCX) isoform 1 inhibitor, SEA0400, on NMDA-activated whole-cell currents and their block by amitriptyline, desipramine and clomipramine recorded by patch-clamp technique in cortical neurons of primary culture were studied. We demonstrated that in the presence of extracellular Ca2+, 50 nM SEA0400 caused a reversible decrease of the steady-state amplitude of NMDAR currents, whereas loading neurons with BAPTA or the removal of extracellular Ca2+ abolished the effect. The decrease did not exceed 30% of the amplitude and did not depend on membrane voltage. The external Mg2+ block and 50 nM SEA0400 inhibition of currents were additive, suggesting their independent modes of action. In the presence of Ca2+ SEA0400 speeded up the decay of NMDAR currents to the steady state determined by CDD. The measured IC50 value of 27nM for SEA0400-induced inhibition coincides with that for NCX1. Presumably, SEA0400 effects are induced by an enhancement of NMDAR CDD through the inhibition of Ca2+ extrusion by NCX1. SEA0400, in addition, at nanomolar concentrations could interfere with Ca2+-dependent effect of tricyclic antidepressants. In the presence of 50nM SEA0400, the IC50s for NMDAR inhibition by amitriptyline and desipramine increased by about 20 folds, as the Ca2+-dependent NMDAR inhibition disappeared. This observation highlights NCX1 involvement in amitriptyline and desipramine effects on NMDARs and unmasks competitive relationships between SEA0400 and these antidepressants. Neither amitriptyline nor desipramine could affect NCX3. The open-channel block of NMDARs by these substances was not affected by SEA0400. In agreement, SEA0400 did not change the IC50 for clomipramine, which acts as a pure NMDAR open-channel blocker. Thus, NCX seems to represent a promising molecular target to treat neurological disorders, because of the ability to modulate NMDARs by decreasing the open probability through the enhancement of their CDD.